Studies of inclusion complexes between cyclodextrins and polyazamacrocyclic chelates of lanthanide (III) ions - Henriques, Elsa S. (2003)
The complexes between [gamma]-cyclodextrin and lanthanide (III) chelates of the polyazamacrocycles DOTA (DOTA [reverse not equivalent] 1,4,7,10-tertraazacyclododecane-1,4,7,10-tetraacetate) and DOTP (DOTP [reverse not equivalent] 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetramethylenephosphonate) have been thought out to enhance the potential of such chelates as contrast agents for MRI. Given the actual demand for the design of new contrast agents, we thought it worthwhile to confirm previous results for the equilibrium constant K obtained by one of us by NMR on the DOTP complex, as well as to determine K for a new one with DOTA. Further, we wanted to study and quantify the interactions present in these complexes, with a view to improve them in newly designed complexes.